From Philosophical Narrative of History to Narrative of Philosophy of History: A Critical Reading of the Book History by the Narrative of Philosophy; From Herodotus to Alain Badiou - Mohsen Alviri (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Thinking about history has increased and gained a wide range of changes in recent decades. If we consider the “Philosophy of History” to be the result of these changes, given the almost great distance between us Iranians and the world level of these studies, the importance of the methodical awareness of new studies and approaches in this issue becomes clear. “History by Narrative of Philosophy: From Herodotus to Alain Badiou”, deserves to be read as an outstanding book in this field because of its characteristics. This article is a critical review of the book in the following topics: the ambiguity of the book’s title, the divergent multiplicity of the book’s purpose, the confusion in the chapters and sub-chapters, the ambiguity of the position of this book among the other works in this field, the obvious lack of paying attention to the Eastern and Islamic heritage, Confusion and inconsistency of the terms related to the currents of thought and finally ambiguity in new definition of history. After reflecting on the technical and editorial aspects of the work, the paper concludes that although the book fails to distinguish between the philosophical narrative of history and narrative of the philosophy of history, and so it has been far from the conventional mentality of historians, but it has many useful benefits for them.